2019
DOI: 10.1002/jgc4.1088
|View full text |Cite
|
Sign up to set email alerts
|

Clinical models of telehealth in genetics: A regional telegenetics landscape

Abstract: The use of live video consultations in genetics has been shown to improve patient access with high satisfaction; however, little is known about the current landscape of clinical telehealth models in the field of genetics (i.e., telegenetics). This survey aimed to address that gap across seven states and the District of Columbia. Among 51 self‐defined telegenetics programs responding to an online survey, 32 currently utilized live videoconferencing as at least one of their technologies (i.e., were “video‐capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 49 publications
(121 reference statements)
3
55
0
Order By: Relevance
“…Previous studies have highlighted both the utility and difficulty of implementing telegenetics services (Greenberg et al, 2020; Zierhut et al, 2018; Zilliacus et al, 2010). For many reasons, such as technological difficulties, communication barriers, and reimbursement limitations, genetic counselors have been slow to adopt the use of telegenetics (Otten, Birnie, Lucassen, Ranchor, & Van Langen, 2016; Terry et al, 2019; Zierhut et al, 2018). However, this changed drastically with the need to accommodate new healthcare delivery methods in response to the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have highlighted both the utility and difficulty of implementing telegenetics services (Greenberg et al, 2020; Zierhut et al, 2018; Zilliacus et al, 2010). For many reasons, such as technological difficulties, communication barriers, and reimbursement limitations, genetic counselors have been slow to adopt the use of telegenetics (Otten, Birnie, Lucassen, Ranchor, & Van Langen, 2016; Terry et al, 2019; Zierhut et al, 2018). However, this changed drastically with the need to accommodate new healthcare delivery methods in response to the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…There are acknowledged challenges to telegenetics consultations, including the inability to perceive patients' nonverbal cues, difficulty performing psychosocial counseling, technology‐related issues, and reimbursement limitations, leading to a historic provider preference for an in‐person model of health care delivery (Terry et al, 2019; Zierhut et al, 2018; Zilliacus et al, 2010). These barriers are not unique to telegenetics as they have been experienced by many healthcare providers exploring telehealth across various specialties (Burke Jr. & Hall, 2015; Dinesen et al, 2016; Moss, Lai, & Ko, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach in this article promoted efficient utilization of the geneticist's time, enabling focus on more complicated cases, and to provide supervision and support for the pediatric diagnostic team. Previous studies have shown that telemedicine reduces cost and time for both the doctor and the patient during encounters, decreases waiting times, improves disease awareness, creates access to specialty care otherwise not available in country, and increases regional reach and referrals to specialty programs (Helou et al, 2020; Hilgart et al, 2012; Hopper et al, 2011; Otten, Birnie, Ranchor, & van Langen, 2016; Terry et al, 2019). Telemedicine can also provide an effective method for genetic consulting and exchange of professional knowledge in between programs (Vrecar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although Project ECHO has not yet been evaluated for its potential to broaden access to clinical genetics services, it holds some promise for increasing reach of these innovations. However, a survey of genetics providers in seven states and the District of Columbia found that insurance covered only about 47% of telegenetics services [70], suggesting that telemedicine is not the panacea that some have expected it to be. For these reasons, our model illustrates the importance of drawing together multiple parties when “changing service sites” or “providing interactive assistance.” In the examples that follow, we illustrate how collaborations among stakeholders across arenas may provide a more complete picture of who is and is not being served, and allow for more creativity in designing programs to reach those groups.…”
Section: Needed Components In An Integrated Multilevel Framework mentioning
confidence: 99%